Hydroponic vegetables: A sustainable food production system and profitable venture under climate change - Khan, Farooq A; Narayan, Sumati; Khan, Faheem U; Dar, Zaffar M; Amir, M; Mouinuddin; Astha (Indian Horticulture, 2023)
Humans require food, water, and living space in order to survive. These do not exist in endless abundance, making humans dependent upon the optimization of land area. Considering that world population is increasing and will reach about 9 billion by 2050, it is evident that food security is one of the pivotal themes of the new millennium & reasonably, the most urgent challenge for the agricultural sector. Food productivity of the current system of cultivation as well as water harvesting are the major concerns. Also, there is a progressive drop of fertile soil surface and quality water due to present trend of global climate change/ uncertainty, environmental pollution and urbanization phenomena, which greatly complicates the context. Infestation by the pathogens under traditional growing system further limits the potential crop production. Thus, farming has to become more productive as well as protective with some advance growing technique, especially under changing climatic situation and areas difficult to cultivate must be adopted. Hydroponics, particularly in the form of vertical farming is a wonderful option that provide the opportunity to grow anywhere with least use of land and water, and without any fear of insect, pest, diseases and other natural calamities. Also, due to the changing global economic scenario, getting jobs in public sector is arduous and private entrepreneurship is a lucrative option. Vegetables are important cash crops that hold the potential of improving both income and nutrition of farmers, and rising demand for vegetables require growing vegetable crops in all possible places and ways.